Structurally colored silica foams using colloidal templating - Manne, Kalpana; Magkiriadou, Sofia; Yazhgur, Pavel; Demirörs, Ahmet F.; Scheffold, Frank (Frontiers in Soft Matter, 2023)
We produce solid silica dry foam structures that exhibit structural color. For this purpose, we use densely packed colloidal microgels decorated with silica nanoparticles that are much smaller than the microgels. By concentrating and overpacking the microgel particles, we can control their morphology so that the silica nanoparticles spontaneously form honeycomb-like structures or networks. We obtain pure silica dry foam structures by burning the organic polymer, leaving behind silica networks. The resulting foams exhibit vivid structural colors. We can control the color by changing the microgel particles’ size and degree of compression. Furthermore, thanks to the softness of the particles, compression can also lead to the appearance of facets. This faceting behavior distinguishes microgels from hard spherical particles. We present details about the synthesis and fabrication strategies and report on a comprehensive characterization of optical and structural properties. Our study provides insight into the fabrication of innovative self-assembled materials with structural colors by colloidal templating.